Ironic effects of suppressing specific and non-specific demography-related thoughts in job candidate evaluations. - Babaii, Aida (UiT Norges arktiske universitet, 2014)
This present work explored the suppression instructions conveyed during an applicant evaluation process. The following experiment predicted that the participants in the specific suppression condition would evaluate the stereotypical applicants less favorably compared to participants in the other conditions. The participants received one of three suppression instructions: one instructed them to suppress all demographic related thought; one instructed them to suppress specific demographic thoughts; a control group where no instructions were given. All the participants then evaluated female and male Italian, Norwegian and Sami applicants for six professions. Before the evaluation task, half of the participants were made cognitively busy while the other half were not. We expected an ironic effect where the busy participants instructed to suppress specific demographic thoughts to evaluate the counter-stereotypic applicants less favorably than the participants in the other conditions. The results did not support the prediction indicating an absence of the ironic effect. A jobwise analysis was conducted to investigate rating difference in the professions. Again, the results did not yield a significant finding. Thus no ironic effect was found in the experiment meaning that the participants rated the applicants equally in all the conditions. Dette studiet utforsket effekter av instrukser om å fortrenge under evalueringen av jobb kandidater. Det følgende eksperimentet undersøkte forskjellen mellom deltagere som fikk instrukser om å fortrenge spesifikke tanker og deltagere som fikk instrukser om å fortrenge demografiske tanker under kognitiv press. Det var forventet at deltagere som ble instruert i å fortrenge spesifikke tanker til å evaluere de stereotypiske kandidatene mindre positivt sammenlignet med de andre deltagerne i andre betingelser. Det ble gitt tre instrukser: en ba deltagerne om fortrenge alle demografiske tanker; en instruerte deltagere til å fortrenge spesifikke demografiske tanker; og en kontroll gruppe ...